ANALISIS PERILAKU KONSUMTIF MILENIAL TERHADAP TREND ARISAN ONLINE MENURUN DALAM EKONOMI ISLAM - Dyana Dwi Kartika Sari; Indah Nurbaiti; Putri Mayangsari; Fatimah Yunus; Khairiah Elwardah (Juremi: Jurnal Riset Ekonomi, 2021)
This research aims to find out the driving factors and dominant factors of millennial consumptive behavior towards the declining online social gathering trend, as well as how millennial consumptive behavior towards the declining online arisan trend based on Islamic consumption principles. This study uses a qualitative description method, the data collection technique is carried out using a non-probability sample technique with a purposive sampling technique. The subjects in this study were Arisan Online Descending participants on the Bengkulu Squad Arisan account in the Pagar Dewa village, Selebar district, Bengkulu city. The results show that 7 out of 10 millennials have consumptive behavior, this is influenced by several factors, including cultural factors, role models, social class and personality. The dominant factor that most influences millennial consumptive behavior in this declining online social gathering is the role model factor. This is not in accordance with the principle of Islamic consumption, namely simplicity.